Polo-like kinase-1 in DNA damage response - Hyun, Sun-Yi; Hwan, Hyo-In; Jang, Young-Joo (BMB reports, 2014)
Polo-like kinase-1 (Plk1) belongs to a family of serine-threonine kinases and plays a critical role in mitotic progression. Plk1 involves in the initiation of mitosis, centrosome maturation, bipolar spindle formation, and cytokinesis, well-reported as traditional functions of Plk1. In this review, we discuss the role of Plk1 during DNA damage response beyond the functions in mitotsis. When DNA is damaged in cells under various stress conditions, the checkpoint mechanism is activated to allow cells to have enough time for repair. When damage is repaired, cells progress continuously their division, which is called checkpoint recovery. If damage is too severe to repair, cells undergo apoptotic pathway. If damage is not completely repaired, cells undergo a process called checkpoint adaptation, and resume cell division cycle with damaged DNA. Plk1 targets and regulates many key factors in the process of damage response, and we deal with these subjects in this review.